2007
DOI: 10.1017/s1368980007702896
|View full text |Cite
|
Sign up to set email alerts
|

‘The bigger the better’ – mothers' social networks and child nutrition in Andhra Pradesh

Abstract: Objective: It is hypothesised that mothers' social networks can positively affect child nutrition through the sharing of health knowledge and other resources. The present study describes the composition of mothers' networks, examines their association with child nutrition, and assesses whether health knowledge is shared within networks. Design and setting: Cross-sectional data for mothers of young children from Andhra Pradesh (south India) were combined with existing data from the Young Lives study, in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 44 publications
5
28
0
Order By: Relevance
“…Third, women were nominated more often than men, and women reported significantly larger social networks than men, consistent with findings of adults in the United States and Australia [55]. Network size and gender composition in our study were consistent with those reported in a social network study of mothers in Southern India, where mean network size was 3.36, 78% of networks were composed of family members, and more female than male ties were nominated among the urban-dwelling sample compared to the rural-dwelling sample [56]. Finally, we found that while the majority (90%) of network ties resided in the same city as the participant, less than 5% of ties were neighbors.…”
Section: Introductionsupporting
confidence: 90%
“…Third, women were nominated more often than men, and women reported significantly larger social networks than men, consistent with findings of adults in the United States and Australia [55]. Network size and gender composition in our study were consistent with those reported in a social network study of mothers in Southern India, where mean network size was 3.36, 78% of networks were composed of family members, and more female than male ties were nominated among the urban-dwelling sample compared to the rural-dwelling sample [56]. Finally, we found that while the majority (90%) of network ties resided in the same city as the participant, less than 5% of ties were neighbors.…”
Section: Introductionsupporting
confidence: 90%
“…Women, in particular, appear to gain significantly from having support networks in place (Hurdle 2001), and women often look to each other as support partners (Adams et al 2002;Hung and Chung 2001;Moestue et al 2007;Savage et al 2007). Social support related to maternal and infant health is a particularly well-researched area, with studies depicting a range of positive benefits (Cohen 1988;Cohen and Syme 1985).…”
mentioning
confidence: 99%
“…Adams et al (2002) show that among women in Mali there is a positive association between network size and child survival. Another study looking at transmission of health information in women's networks shows that women in India with larger and more literate networks had children with greater height-for-age Z scores (Moestue et al 2007).…”
mentioning
confidence: 99%
“…Cleland and Jejeebhoy [49] also report lower fertility rates amongst women with little or no education but living in educated communities, compared to similarly educated women living in communities with lower overall education. Moestue, Huttly, Sarella et al [50] use a unique dataset on mothers’ networks to show that mothers from poorest household benefit the most from having a more ‘literate’ network in improving child health. Based on these findings, community-level factors are explicitly controlled for while modelling child health, and are the secondary variables of interest in this paper.…”
Section: Child Healthmentioning
confidence: 99%